2009
DOI: 10.3109/00365520903486109
|View full text |Cite
|
Sign up to set email alerts
|

Is transcatheter arterial embolization a safer alternative than surgery when endoscopic therapy fails in bleeding duodenal ulcer?

Abstract: TAE of the gastroduodenal artery appears to be a safe alternative when endoscopic therapy for bleeding duodenal ulcer fails, at least in high-risk patients. The role of TAE in low-risk patients with bleeding from duodenal ulcer needs to be defined by means of a prospective controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 21 publications
2
44
1
4
Order By: Relevance
“…The findings in this study appear to confirm previously published retrospective case series that support the role of TAE and show it reduces the need for surgery, has a low complication rate, and does not increase mortality [66][67][68][69]. Indeed, four other retrospective studies compared the two techniques and showed at least similar efficacy in terms of rate of rebleeding, morbidity, and mortality, whereas there was a bias of selection since TAE was preferentially used for high surgical risk patients.…”
Section: Topics Of Interest Embolization Versus Surgerysupporting
confidence: 89%
See 1 more Smart Citation
“…The findings in this study appear to confirm previously published retrospective case series that support the role of TAE and show it reduces the need for surgery, has a low complication rate, and does not increase mortality [66][67][68][69]. Indeed, four other retrospective studies compared the two techniques and showed at least similar efficacy in terms of rate of rebleeding, morbidity, and mortality, whereas there was a bias of selection since TAE was preferentially used for high surgical risk patients.…”
Section: Topics Of Interest Embolization Versus Surgerysupporting
confidence: 89%
“…Thirty-day mortality was lower in the TAE group (3% versus 14%). More recently, Venclauskas et al [67] compared these two treatment strategies. Arterial embolization was performed in 24 patients and open surgery in 50 patients after unsuccessful endoscopic therapy for bleeding duodenal ulcers.…”
Section: Topics Of Interest Embolization Versus Surgerymentioning
confidence: 98%
“…There was no difference in 30-day mortality between the two groups (25.0% vs 30.4%, P 5 .77), 62 a result consistent with several other retrospective studies. [63][64][65] The preliminary results of a randomized study in patients with massive bleeding uncontrolled by endoscopy showed an insignificantly higher failure rate with TAE than surgery (52.9% vs 21.4%, P 5 .052), despite similar outcomes in terms of hospitalization and mortality between the two groups. 66 …”
Section: Acute Management Of Rebleedingmentioning
confidence: 92%
“…Ces chiffres sont superposables à ceux de la chirurgie. Ainsi, quatre études rétrospectives ayant comparé l'efficacité thérapeutique et la morbi-mortalité post-procédure du traitement chirugical versus traitement endovasculaire retrouvent une efficacité similaire en termes de taux de resaignement, de mortalité et de morbidité post-procédure [7][8][9][10]. Toutefois, ces résultats sont à pondérer par l'existence de biais de sélection, l'embolisation étant proposée à une population plus âgée, avec plus de comorbidités, voire une coagulopathie surajoutée en rapport avec la prise d'anticoagulants.…”
Section: Introductionunclassified